PERAN SENYAWA KATEKIN DALAM PENURUNAN BERAT BADAN PADA OBESITAS - Deralitha Meilinia Shavitri Shavitri (Yayasan Pendidikan Medika Indonesia, 2022)
Obesity is a condition where there is an excessive accumulation of body fat tissue. Obesity is considered a disease and a risk factor for other diseases. In Indonesia, 28.7% of adults aged 18 years and over are obese (BMI 25), and based on the 2015-2019 RPJMN indicators as many as 15.4% are obese (BMI > 27). Catechins are polyphenolic flavonoids that have broad biological functions and good health effects. In particular, epigallocatechin-3gallate(EGCG) can reduce body weight and body fat accumulation by increasing energy expenditure and fat oxidation.